ANALISIS GAYA KEPEMIMPINAN KEPALA DINAS KESEHATAN PROVINSI SULAWESI TENGAH - Srilulu, Srilulu (Katalogis, 2015)
This research is conducted to analyze the leadership style of the Health Agency Director of Central Sulawesi. This research uses a leadership style according Lippit & White namely, Autocratic, Democratic and Laissez Faire. The method used in this research is descriptive qualitative, ie to obtain a detailed description of how the leadership style of the Health Agency Director of Central Sulawesi, by using seven informants. Data collection was conducted using interview, observation, and documentation instrument. The operational concept of this research is the leadership style of the Agency Director that includes: 1. Authoritarian style, where all the policies are set by the director himself and the execution is assigned to a subordinate. 2. Democratic style, where a leader always involves all members of the group in making decisions. 3. Laissez Faire style, in this type, the leader provides the widest possible freedom to every member of staff in the planning procedure and what will be done for the discharge of the duties of their office. The result shows that the Democratic leadership is more dominant applied by the head of Health Agency of Central Sulawesi, while the autocracy style and Laissez Faire style is only used for specific situations.